2015
DOI: 10.1111/eos.12228
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/orphanin FQ up‐regulates P2X3 receptors in primary cultures of neonatal rat trigeminal ganglion neurons

Abstract: Recent evidence indicates a nociceptive role of the nociceptin/orphanin FQ-opioid receptor-like receptor (N/OFQ-ORL1) system in craniofacial pain; however, the mechanisms of such an effect remain unclear. We investigated whether the action of N/OFQ involves the modulation of P2X3 , a pain-transducing ionotropic receptor. Double-labeled immunohistochemical staining was used to determine the co-localization of ORL1 and P2X3 receptors in the trigeminal ganglia (TG) of neonatal Sprague-Dawley rats. The effect of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…This nding was consistent with our previous studies where we found that periodontal administration of N/OFQ antagonist UFP-101 was able to alleviate pain in rats and that N/OFQ could upregulate the expression of a nociceptor P2X3 (16,33). However, Borgland et al revealed that N/OFQ inhibited calcium currents of trigeminal neurons, supporting its antinociceptive role in TG (34).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This nding was consistent with our previous studies where we found that periodontal administration of N/OFQ antagonist UFP-101 was able to alleviate pain in rats and that N/OFQ could upregulate the expression of a nociceptor P2X3 (16,33). However, Borgland et al revealed that N/OFQ inhibited calcium currents of trigeminal neurons, supporting its antinociceptive role in TG (34).…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies have reported that N/OFQ participates in pain modulation at periodontium and trigeminal nucleus caudalis (16,32). Although previous ndings have demonstrated that N/OFQ and its receptor are actively expressed in neuronal cells of trigeminal ganglia and our previous study found an indirect evidence that N/OFQ could modulate the expression of a key nociceptor (P2X3) on trigeminal neurons (22,33), its pain-modulatory role at TG is still largely unknown. Our results revealed that intra-ganglionic administration of N/OFQ exacerbated pain while that of UFP-101 alleviated pain, suggesting that N/OFQ plays a pro-nociceptive role in orofacial pain induced by tooth movement.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, elevated pain level caused by PNOC overexpression lentivirus was strongly correlated with increased N/OFQ expression, strongly supporting the promotive role of N/OFQ in pain modulation. This nding was consistent with our previous studies where we found that periodontal administration of N/OFQ antagonist UFP-101 was able to alleviate pain in rats and that N/OFQ could upregulate the expression of a nociceptor P2X3 (16,35). However, Borgland et al revealed that N/OFQ inhibited calcium currents of trigeminal neurons, supporting its antinociceptive role in TG (36).…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies have reported that N/OFQ participates in pain modulation at periodontium and trigeminal nucleus caudalis (16,34). Although previous ndings have demonstrated that N/OFQ and its receptor are actively expressed in neuronal cells of trigeminal ganglia and our previous study found an indirect evidence that N/OFQ could modulate the expression of a key nociceptor (P2X3) on trigeminal neurons (22,35), its pain-modulatory role at TG is still largely unknown. Our results revealed that intra-ganglionic administration of N/OFQ exacerbated pain while that of UFP-101 alleviated pain, suggesting that N/OFQ plays a pro-nociceptive role in orofacial pain induced by tooth movement.…”
Section: Discussionmentioning
confidence: 88%
“…P2X3 receptors are only one of multitudinous neurotransmitter media such as Substance P, N-methyl-D-aspartate receptor, transient receptor potential vanilloid type 1 (TRPV1), calcitonin gene-related peptide (CGRP), etc. [Stanchev et al, 2009;Krimon et al, 2013;Wang et al, 2015].…”
Section: Down-regulated Under Smf Following Experimental Tooth Movemementioning
confidence: 99%